Założenia psychologii pozytywnej jako teoretyczna podstawa zastosowania metody teatru terapeutycznego w pracy z osobami z niepełnosprawnością intelektualną = Assumptions of positive psychology as a theoretical basis for the application of the therapeutic theater method in work with people with intellectual disabilities - Mróz, Anna; Żeszko-Majewska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The postulates of positive psychology break the pattern of thinking according to which mental health was defined by the lack of symptoms of a disorder classified in relation to the statistical norm. In a positive sense, health is the ability to discover and realize individual development potentials in pursuit of an engaged and fulfilled life. Therapeutic theater is a space that allows people with intellectual disabilities to explore their own developmental resources and expand the possibilities of their expression. Properly conducted therapeutic work not only helps to build a sense of agency and experience satisfaction from one`s own involvement, but also creates the possibility of natural cooperation and integration between participants, regardless of their age and diagnosed dysfunctions. The article presents the basic principles of working with the use of theatrical techniques together with examples illustrating them.
Keywords: psychologia pozytywna; teatr terapeutyczny; niepełnosprawność intelektualna; positive psychology; therapeutic theatre; intellectual disability